2018
DOI: 10.3390/v10090486
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Distinct Alphacoronaviruses in Five Different Bat Species in Denmark

Abstract: Bat populations harbour a multitude of viruses; some of these are pathogenic or potentially pathogenic in other animals or humans. Therefore, it is important to monitor the populations and characterize these viruses. In this study, the presence of coronaviruses (CoVs) in different species of Danish bats was investigated using active surveillance at different geographical locations in Denmark. Faecal samples were screened for the presence of CoVs using pan-CoV real-time RT-PCR assays. The amplicons, obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 27 publications
5
27
0
Order By: Relevance
“…Our results correspond to a recent study investigating frugivorous and insectivorous bats in Lao PDR and Cambodia, where a varying degree of host specificity in the detected astrovirus sequences was found [ 15 ]. Similar results of host restriction were found for other RNA viruses, i.e., alphacoronaviruses in Denmark [ 29 ]. The study revealed high host restriction and a close resemblance between the Danish M.daubentonii bat CoVs and British and German alphacoronaviruses even located roughly 330 km from each other, whereas other distinct Danish bat CoV sequences were present within each of the five bat species included in the study.…”
Section: Discussionsupporting
confidence: 82%
“…Our results correspond to a recent study investigating frugivorous and insectivorous bats in Lao PDR and Cambodia, where a varying degree of host specificity in the detected astrovirus sequences was found [ 15 ]. Similar results of host restriction were found for other RNA viruses, i.e., alphacoronaviruses in Denmark [ 29 ]. The study revealed high host restriction and a close resemblance between the Danish M.daubentonii bat CoVs and British and German alphacoronaviruses even located roughly 330 km from each other, whereas other distinct Danish bat CoV sequences were present within each of the five bat species included in the study.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, the prevalence of alphacoronaviruses was approximately seven times higher. It is likely that bats are more susceptible to—and wider hosts of—alphacoronavius than betacoronavirus (Anthony et al., 2017; Lazov et al., 2018; Lin et al., 2017; Wacharapluesadee et al., 2015). To date, seven of twenty‐four Korean bat species were found to be associated with alphacoronaviruses, and only four species were found to be associated with betacoronaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Since the emergence of SARS‐CoV in 2003 and MERS‐CoV in 2012, several studies have shown that bat CoVs are found in North and South America, Europe, Africa, Australia and Asia (Gouilh et al., 2018; August, Mathews, & Nunn, 2012; Carrington et al., 2008; De Sabato et al., 2019; Dominguez, O’Shea, Oko, & Holmes, 2007; Lazov et al., 2018; Liang et al., 2017; Lin et al., 2017; Rizzo et al., 2017; Smith et al., 2016; Tang et al., 2006; Tao et al., 2012; Wacharapluesadee et al., 2015; Watanabe et al., 2010; Woo et al., 2006). In South Korea, SARS‐like and MERS‐like coronaviruses were reported in bat faeces since 2015 (Kim et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Reports of coronaviruses in bats from the Nordic countries are limited. Previously, partial coronavirus ORF1b sequences from five different bat species in Denmark were reported [27] and, more recently, full-genome sequences of two separate coronaviruses-from Myotis daubentonii and Myotis brandtii-as well as other partial bat coronavirus (BtCoV) sequences, have been determined [28]. Still missing are full-genome sequences of coronaviruses from other bat species in the Nordic countries.…”
Section: Introductionmentioning
confidence: 99%